Glioblastoma-derived Leptin Induces Tube Formation and Growth of Endothelial Cells: Comparison with VEGF Effects - Ferla, Rita (BioMed Central, 2011)
BACKGROUND: Leptin is a pleiotropic hormone whose mitogenic and angiogenic activity has been implicated in the development and progression of several malignancies, including brain tumors. In human brain cancer, especially in glioblastoma multiforme (GBM), leptin and its receptor (ObR) are overexpressed relative to normal tissue. Until present, the potential of intratumoral leptin to exert proangiogenic effects on endothelial cells has not been addressed. Using in vitro models, we investigated if GBM can express leptin, if leptin can affect angiogenic and mitogenic potential of endothelial cells, and if its action can be inhibited with specific ObR antagonists. Leptin effects were compared with that induced by the best-characterized angiogenic regulator, VEGF. RESULTS: We found that GBM cell lines LN18 and LN229 express leptin mRNA and LN18 cells secrete detectable amounts of leptin protein. Both lines also expressed and secreted VEGF. The conditioned medium (CM) of LN18 and LN 229 cultures as well as 200 ng/mL pure leptin or 50 ng/mL pure VEGF stimulated proliferation of human umbilical vein endothelial cells (HUVEC) at 24 h of treatment. Mitogenic effects of CM were ~2-fold greater than that of pure growth factors. Furthermore, CM treatment of HUVEC for 24 h increased tube formation by ~5.5-fold, while leptin increased tube formation by ~ 80% and VEGF by ~60% at 8 h. The mitogenic and angiogenic effects of both CM were blocked by Aca 1, a peptide ObR antagonist, and by SU1498, which inhibits the VEGF receptor. The best anti-angiogenic and cytostatic effects of Aca1 were obtained with 10 nM and 25 nM, respectively, while for SU1498, the best growth and angiogenic inhibition was observed at 5 μM. The combination of 5 μM SU1498 and Aca1 at 25 nM (growth inhibition) or at 10 nM (reduction of tube formation) produced superior effects compared with single agent treatments. CONCLUSIONS: Our data provide the first evidence that LN18 and LN 229 human GBM cells express leptin mRNA and might produce biologically active leptin, which can stimulate tube formation and enhance proliferation of endothelial cells. Furthermore, we demonstrate for the first time that a peptide ObR antagonist inhibits proangiogenic and growth effects of leptin on endothelial cells, and that the pharmacological potential of this compound might be combined with drugs targeting the VEGF pathway.